2005
DOI: 10.1029/2005gl023484
|View full text |Cite
|
Sign up to set email alerts
|

Cold compaction of water ice

Abstract: [1] Hydrostatic compaction of granulated water ice was measured in laboratory experiments at temperatures 77 K to 120 K. We performed step-wise hydrostatic pressurization tests on 5 samples to maximum pressures P of 150 MPa, using relatively tight (0.18 -0.25 mm) and broad (0.25 -2.0 mm) starting grain-size distributions. Compaction change of volume is highly nonlinear in P, typical for brittle, granular materials. No time-dependent creep occurred on the lab time scale. Significant residual porosity ($0.10) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 17 publications
2
54
0
Order By: Relevance
“…This is supported by theory (Weidenschilling 1997;Wahlberg Jansson & Johansen 2014), remote observations (Weissman & Lowry 2008;Baer et al 2011), meteorite samples (Consolmagno et al 2008;Macke 2010), and laboratory experiments (Leliwa-Kopystyński et al 1994;Durham et al 2005;Yasui & Arakawa 2009). Jura & Xu (2010) assume that the bulk density of Ceres (2.1 g cm −3 ) represents the typical bulk density of small or intermediate sized icy bodies.…”
Section: Previous Studiesmentioning
confidence: 74%
“…This is supported by theory (Weidenschilling 1997;Wahlberg Jansson & Johansen 2014), remote observations (Weissman & Lowry 2008;Baer et al 2011), meteorite samples (Consolmagno et al 2008;Macke 2010), and laboratory experiments (Leliwa-Kopystyński et al 1994;Durham et al 2005;Yasui & Arakawa 2009). Jura & Xu (2010) assume that the bulk density of Ceres (2.1 g cm −3 ) represents the typical bulk density of small or intermediate sized icy bodies.…”
Section: Previous Studiesmentioning
confidence: 74%
“…The compaction experiments have been conducted on water ice, quartz sand, and mixtures of water ice and silicate materials [ Maeno , 1982; Durham et al , 2005; Karner et al , 2003; Leliwa‐Kopystynski et al , 1994]. Maeno [1982] studied the snow compaction process of the south polar glacier on Earth and found that the compaction process can be divided into four stages on the basis of the slope of the density profile.…”
Section: Introductionmentioning
confidence: 99%
“…According to this theory, compaction depends on several factors such as temperature, stress, and grain size. Furthermore, Durham et al [2005] performed compaction experiments on water ice using icy grains of various sizes at temperatures of −153 and −196°C; they found that the compaction behavior, represented as the relationship between pressure and density, was explained by the failure of the ice grain and was independent of temperature and ice grain size. Karner et al [2003] performed hydrostatic compaction experiments of quartz sands and found that the compaction mechanisms changed with pressure; these mechanisms involve rearrangement, elastic deformation, and cracking and failure.…”
Section: Introductionmentioning
confidence: 99%
“…Orcus is then assumed to have a 475 km radius, a 19.9% albedo , and a bulk density of 1900 kg m −3 . By assuming a residual porosity of 10% (Durham et al 2005), this density leads to a mixture made of 77% of dust and 23% of water ice (mass fractions), the dust being homogeneously distributed within the ice matrix. The resulting thermal properties are: the thermal conductivity κ = 0.18 Wm −1 K −1 , the heat capacity c = 10 3 Jkg −1 K −1 .…”
Section: The Modelmentioning
confidence: 99%